X-ray CT images of IODP Hole 386-M0081C - Strasser, Michael; Ikehara, Ken; Everest, Jeremy D; Maeda, Lena; Hochmuth, Katharina; Grant, Hannah; Stewart, Margaret S; Sakurai, Noriaki; Yokoyama, Takahiro; Bao, Rui; Bellanova, Piero; Brunet, Morgane; et al. (PANGAEA, 2025)
Collection of X-ray Computed Tomography (CT) images from the above given hole of International Ocean Discovery Program (IODP) Expedition 386 (Japan Trench Paleoseismology). The offshore phase of this expedition took place between 2021-04-13 and 2021-06-01 onboard Japanese R/V Kaimei from and to Yokosuka, Japan. This was followed by an onshore phase onboard D/V Chikyu between 2022-02-14 – 2022-03-15. X-ray CT scanning was performed on whole-round sections on board D/V Chikyu in July 2021, after the offshore phase and prior to the onshore phase, using a Discovery CT 750HD (GE Medical Systems) that produces 32 0.625 mm thick slice images every 0.4 s. Data generated for each core consist of core-axis-normal planes of X-ray attenuation values that are 512 × 512 pixels in size. Data were stored on the server as DICOM formatted files. The DICOM files were restructured to create 3-D images for further investigation. For publication purposes JPG files of each scanned section were produced imaging the plane representative of the split core surface. For further methodological information see methods chapter in Strasser, M. et al., 2023 https://doi.org/10.14379/iodp.proc.386.102.2023
Keywords: Computed Tomography; International Ocean Discovery Program (IODP); IODP; Japan Trench